Germany's colonial pasts - Ames, Eric, 1969-; Klotz, Marcia, 1961-; Wildenthal, Lora, 1965- (University of Nebraska Press, 2005)
'Germany's Colonial Pasts' is a wide-ranging study of German colonialism and its legacies.
Keywords: German literature -- 19th century -- History and criticism.; German literature -- 20th century -- History and criticism.; Nationalism -- Germany -- History.; National characteristics, German, in literature.; Imperialism -- History -- 19th century.; Germany -- Foreign relations -- 1918-; Colonies in literature.; Nationalism in literature.; Germans in literature.; Littérature allemande -- 19e siècle -- Histoire et critique.; Littérature allemande -- 20e siècle -- Histoire et critique.; Nationalisme -- Allemagne -- Histoire.; Allemands dans la littérature.; Impérialisme -- Histoire -- 19e siècle.; Colonies dans la littérature.; Nationalisme dans la littérature.; Allemagne -- Relations extérieures -- 1918-; LITERARY CRITICISM -- European -- German.; Germans in literature; Colonies in literature; Diplomatic relations; German literature; Imperialism; National characteristics, German, in literature; Nationalism; Nationalism in literature; Germany; Literatur; Kolonialismus -- Motiv; Kolonialismus; Kultur; Deutschland; Duitse koloniën.; Kolonialisme.; Deutsch.; 15.50 general world history; history of great parts of the world, peoples, civilizations: general.; Since 1800; German colonialism; Criticism, interpretation, etc.; History; Aufsatzsammlung.